Factors Contributing to Kerosene Oil Poisoning in Children - Singh, Arun Kumar; Gurung, P.K. (Journal of BP Koirala Institute of Health Sciences, 2018)
Introduction: Kerosene has been identified as the most common cause of accidental poisoning around the world with majority occurring to either lower or middle income countries. Kerosene poisoning is identified as the fourth leading cause of injury related mortality in children with highest risk for acute poisoning occurring in child under five years of age. Objectives: To identify common factors responsible for exposure to kerosene oil poisoning, its presenting features and outcomes in children. Methods: This was a descriptive study conducted in Department of Pediatrics and Emergency Department, Mayo Hospital / King Edward Medical University Lahore, Pakistan from March to September 2015. Sixty children between the ages of 6 months to 10 years with history of kerosene oil ingestion/ poisoning were enrolled in the study. Information was obtained from guardians or parents. Results: Sixty patients with history of kerosene poisoning were seen during the summer season. Age ranged from 6 months to 10 years. Most patients were from the ages 1 and 3 years and 75% were boys. Most children were from poor socioeconomic condition. The containers were soft drink bottles and plastic bottles; and kitchen and stairs were the common sites of storage. Clinical presentations were cough, vomiting and tachypnea. One child in study died after 8 hours secondary to respiratory complication. Conclusion: Kerosene oil is a common health hazardous substance ingested accidentally by children. There is a need to create public awareness regarding kerosene oil storage and accessibility at home from the younger children.